Kekerasan Kolektif dan Dialog Kebudayaan: Belajar Dari Pengalaman Kekerasan Menjelang Reformasi di Indonesia - Moh. Soehadha (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
This article unravels the causes, the patterns and the solutions of collective violence in Indonesia. The study uses data rooted from the historical experience of collective violence that occurred from 1995 to 1997, prior to the 1998’s Indonesian Reform. The experience of violence in Indonesia that occurred in quick succession before the reform era became a historical document on the causes and patterns of violence, so it could be discussed to find a solution to the violence in Indonesia in the future. The analysis showed that there is violence’s potential rooted in culture. In anthropological view, the concept of "culture of peace" becomes part of a study of local wisdom. It is safe to say that the concept the culture bears the system of symbolic or ethos of violence, at the same time it also holds the ethos of culture of peace. The causes of violence in Indonesia could be analyzed from the cultural mechanisms that legitimize violence. Thus, the solution of the violence could also be searched by studying mechanism that legitimizes the culture of peace.